PEMBUATAN PESTISIDA NABATI DAN APLIKASINYA PADA HAMA ULAT API - Sri Ngapiyatun; Nur Hidayat; Fadli Mulyadi (Politeknik Pertanian Negeri Samarinda, 2017)
This study aims to see the effectiveness of vegetable pesticides from soursop seeds and peppercorns in controlling caterpillar pests that attack palm oil crops. The research was conducted at Soil and Water Laboratory, and in Muara Badak oil palm plantation, the duration of 2 months research from 29 April to 29 June 2017, covering preparation of tools and materials, making and application of vegetable pesticide and data collection.This study used a complete randomized design, consisting of 3 treatment extracts namely control (K0), Soursop seed (K1), and pepper seed (K2), which was repeated 5 times.The results showed that the treatment of vegetable pesticide extract from seeds of soursop and pepper seeds did not give a real effect in controlling caterpillar pests.